Exploring transcriptional regulators Ref-1 and STAT3 as therapeutic targets in malignant peripheral nerve sheath tumours - Gampala, Silpa; Shah, Fenil; Zhang, Chi; Rhodes, Steven D.; Babb, Olivia; Grimard, Michelle; Wireman, Randall S.; Rad, Ellie; Calver, Brian; Bai, Ren-Yuan; Staedtke, Verena; Hulsey, Emily L.; et al. (British journal of cancer, 2021)
Background MPNST is a rare soft-tissue sarcoma that can arise from patients with NF1. Existing chemotherapeutic and targeted agents have been unsuccessful in MPNST treatment, and recent findings implicate STAT3 and HIF1-α in driving MPNST. The DNA-binding and transcriptional activity of both STAT3 and HIF1-α is regulated by Redox factor-1 (Ref-1) redox function. A first-generation Ref-1 inhibitor, APX3330, is being tested in cancer clinical trials and could be applied to MPNST. Methods We characterised Ref-1 and p-STAT3 expression in various MPNST models. Tumour growth, as well as biomarkers of apoptosis and signalling pathways, were measured by qPCR and western blot following treatment with inhibitors of Ref-1 or STAT3. Results MPNSTs from Nf1-Arf flox/flox PostnCre mice exhibit significantly increased positivity of p-STAT3 and Ref-1 expression when malignant transformation occurs. Inhibition of Ref-1 or STAT3 impairs MPNST growth in vitro and in vivo and induces apoptosis. Genes highly expressed in MPNST patients are downregulated following inhibition of Ref-1 or STAT3. Several biomarkers downstream of Ref-1 or STAT3 were also downregulated following Ref-1 or STAT3 inhibition. Conclusions Our findings implicate a unique therapeutic approach to target important MPNST signalling nodes in sarcomas using new first-in-class small molecules for potential translation to the clinic.